Devolution of Power Plan in Pakistan by General Musharraf - Syeda Asmat Zahra Naqvi (Research Parks Publishing LLC, 2021)
Pakistan is a democratic country but since its inception, it has deprived political background particularly in local self-Government. Pakistan’s history shows us that inconsistent civilian rules hindered the process of a viable democratic culture across all level. Time and again military engulfed the civilian political romance. Each military generals introduced the local self-government , General Ayyub introduced Basic democratic system in his regime, General Zia also introduced local government, their main aim was only to legitimize their own powers. But in last military coup by General Musharraf on 1999, the decentralization reforms in Pakistan can be seen